Witch hunt : it happened in Salem Village - Krensky, Stephen; Watling, James (New York : Random House, 1989)
An account of the madness that overtook Salem Village, Massachusetts, when several young girls accused a number of adults in the community of being witches.
5.3
K-3
K-3
Wilson's Children
Elem. School Library Collection
Child Study Children's Book Committee
Keywords: Witchcraft -- Massachusetts -- Salem -- Juvenile literature; Witchcraft -- Massachusetts -- Salem; Witchcraft -- History; Salem (Mass.) -- Social life and customs -- Juvenile literature; Salem (Mass.) -- History -- Colonial period, ca. 1600-1775.; Salem (Mass.) -- History